A longitudinal analysis of early language difficulty and peer problems on later emotional difficulties in adolescence: Evidence from the Millennium Cohort Study. (August 2018) - Forrest, Claire L; Gibson, Jenny L; Halligan, Sarah L; St Clair, Michelle C
Background and aim: Individuals with developmental language disorder have been found to exhibit increased emotional difficulties compared to their typically developed peers. However, the underlying pathways involved in this relationship are unclear. It may be that poor language leads to social exclusion, resulting in feelings of frustration and isolation. Additionally, previous research has focused on clinical samples or early childhood in population cohorts. Therefore, the current paper examines the mediating effect of childhood peer problems on poor emotional outcomes in adolescence using a population cohort. Methods: Data from the Millennium Cohort Study were analysed at ages 5, 7 and 14. The risk of developmental language disorder group (children considered at risk of developing developmental language disorder based on parental report of difficulties or a score −1.5 standard deviation on Naming Vocabulary subtest at age 5) was compared to a general population group. A Sobel–Goodman test was used to examine the mediating effect of teacher-reported peer problems at age 7 on the association between language difficulties at age 5 and parent-reported emotional problems at age 7 and 14. Results: Peer problems at age 7 accounted for approximately 14% of the effect of language difficulties at age 5 on emotional problems at age 7, and approximately 17% of the effect of language difficulties at age 5 on emotional problems at age 14. Conclusions: This paper supports previous findings that children and adolescents with language difficulties are at increased risk for social and emotional problems as reported by their parents and teachers. Furthermore, the findings show that peer problems partially mediate the relationship between language difficulties and emotional problems, suggesting that better relationships with peers may offer some protection against poor mental health outcomes in adolescents at risk of developmental language disorder. Implications: This paper adds to the literature that investigates the mechanisms involved in the relationship between developmental language disorder and increased emotional problems. Practitioners wishing to reduce risk of emotional difficulties in children with developmental language disorder may wish to reflect on what they can do to support a child to develop positive peer relationships.